Image, Music, Text: An Interview with Jeannette Armstrong - Beeler, Karin (Studies in Canadian Literature, 1996)
Jeannette Armstrong speaks about the challenges that her different forms of discourse (the novel, poetry, visual art, music) present. Each work has a separate set of responsibilities, but she has trouble separating the disciplines because the creative process does not differentiate. Across all of her works, she finds ways to deliver information or to create a point of view which requires an emotional response as well as an intellectual response.